Total synthesis and biological evaluation of Koshidacin B, TAN-1746, and Ac-TAN-1746 - Xiong-En Long; Hailiang Xing; Yixin He; Xuanli Meng; Yanling Ma; Chang Liu; Xi Cao; Huiru Nan; Min-Jing Cheng; Jia-Lei Yan; Junyang Liu (BMC Chemistry)
Abstract Analogues of chlamydocin derivatives consistently demonstrate multifaceted bioactivities, particularly through HDAC inhibition mechanisms, oncolytic efficacy, and neuronal preservation capacities. These activities primarily originate from their unique cyclic tetrapeptide scaffold and functional groups within the side chains that enable specific interactions with biomacromolecules. We herein report the total syntheses of three naturally occurring chlamydocin analogues—koshidacin B, TAN-1746, and Ac-TAN-1746. The synthetic strategy employed a modular approach that involved modifying a common intermediate via late-stage olefin cross-metathesis to install the requisite side-chain fragments. This versatile approach enabled an efficient and divergent total synthesis of the target compounds, completing the syntheses in a longest linear sequence of 9–10 steps. Remarkably, TAN-1746 and Ac-TAN-1746 demonstrated significant anti-osteosarcoma activity that exceeded the potency of clinically employed cisplatin—an observation not previously documented. These results strongly validate the utility of the chlamydocin scaffold as a platform for the development of potent inhibitors with promising therapeutic potential. Graphical Abstract